2013
DOI: 10.1364/oe.21.017711
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lateral and axial flow imaging with optical coherence microscopy and tomography

Abstract: Optical coherence tomography (OCT) and optical coherence microscopy (OCM) allow the acquisition of quantitative three-dimensional axial flow by estimating the Doppler shift caused by moving scatterers. Measuring the velocity of red blood cells is currently the principal application of these methods. In many biological tissues, blood flow is often perpendicular to the optical axis, creating the need for a quantitative measurement of lateral flow. Previous work has shown that lateral flow can be measured from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
(54 reference statements)
1
39
0
Order By: Relevance
“…To our knowledge, the contrast revealed by D-FF-OCT is therefore quite unique. Similar dynamic measurements in OCT mainly focus on the blood flow velocity [116,133,134], even with high transverse resolution [135] similar to ours, but, to our knowledge, they never directly show dynamic signals coming from intracellular dynamics. We are wondering whether it comes from a loss in the signal collection due to the use of lower NA illumination, from a difference in the algorithms used (if only blood flow was expected), or from a difference in the exposure time per pixel.…”
Section: Dynamic Ff-octsupporting
confidence: 62%
“…To our knowledge, the contrast revealed by D-FF-OCT is therefore quite unique. Similar dynamic measurements in OCT mainly focus on the blood flow velocity [116,133,134], even with high transverse resolution [135] similar to ours, but, to our knowledge, they never directly show dynamic signals coming from intracellular dynamics. We are wondering whether it comes from a loss in the signal collection due to the use of lower NA illumination, from a difference in the algorithms used (if only blood flow was expected), or from a difference in the exposure time per pixel.…”
Section: Dynamic Ff-octsupporting
confidence: 62%
“…Since the RNFL is damaged in glaucoma-the second leading cause of blindness worldwide [132]-and since RNFL birefringence is connected to layer integrity [133,134], the polarization properties of the RNFL were investigated as potential diagnostic markers for glaucoma. PS-OCT based assessment of the RNFL's birefringent properties might be particularly interesting since it was shown that polarization changes in experimental glaucoma can be observed earlier than RNFL thickness changes [135].…”
Section: Ps-oct In the Eyementioning
confidence: 99%
“…These parameters are extracted by adapting a joint Spectral and Time domain approach (jSTD) to get the axial and transversal velocities [35,36]. C-scans of 128x4096x1024 pixels were acquired by scanning laterally over 200x200 µm.…”
Section: 32mentioning
confidence: 99%
“…Vessels were segmented by applying thresholding and morphological operators. Blood velocity was computed using the axial and transversal velocity components to get the so-called total velocity [36,37]. The median flow velocities over vessel cross-sections were performed to get an estimated velocity.…”
Section: 32mentioning
confidence: 99%